Research and advanced technology for digital libraries : 20th European Conference, ECDL 2016, Hannover, Germany, September 5-9, 2016 ; proceedings /: 20th European Conference, ECDL 2016, Hannover, Germany, September 5-9, 2016 ; proceedings. (2016) - Unknown
No abstract available